Resolva:
Soluções para a tarefa
Respondido por
2
lembrando que
![\boxed{\boxed{a^{log_b(c)}= c^{log_b(a)}}} \boxed{\boxed{a^{log_b(c)}= c^{log_b(a)}}}](https://tex.z-dn.net/?f=%5Cboxed%7B%5Cboxed%7Ba%5E%7Blog_b%28c%29%7D%3D+c%5E%7Blog_b%28a%29%7D%7D%7D)
então
![25^{log_5(2)} = 2^{log_5(25)} = 2^{log_5(5^2)} = 2^{2*log_5(5)} = 2^2 = 4 25^{log_5(2)} = 2^{log_5(25)} = 2^{log_5(5^2)} = 2^{2*log_5(5)} = 2^2 = 4](https://tex.z-dn.net/?f=25%5E%7Blog_5%282%29%7D+%3D+2%5E%7Blog_5%2825%29%7D+%3D+2%5E%7Blog_5%285%5E2%29%7D+%3D+2%5E%7B2%2Alog_5%285%29%7D+%3D+2%5E2+%3D+4)
então
MarioPaiter:
Muito bom.
Perguntas interessantes
Inglês,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Física,
1 ano atrás
Português,
1 ano atrás